Opportunities for quantitative translational modelling in oncology - Yates, JWT; Byrne, H; Chapman, SC; Chen, T; Cucurull-Sanchez, L; Delgado-SanMartin, J; di Veroli, G; Dovedi, SJ; Dunlop, C; Jena, R; Jodrell, D; Martin, E; et al. (American Society for Clinical Pharmacology and Therapeutics, 2020)
A 2‐day meeting was held by members of the UK Quantitative Systems Pharmacology Network (<http://www.qsp‐uk.net/>) in November 2018 on the topic of Translational Challenges in Oncology. Participants from a wide range of backgrounds were invited to discuss current and emerging modeling applications in nonclinical and clinical drug development, and to identify areas for improvement. This resulting perspective explores opportunities for impactful quantitative pharmacology approaches. Four key themes arose from the presentations and discussions that were held, leading to the following recommendations: